Android based dot-matrix led display scrolling text console - Muhamad Azami Fitri, Ab Manan (2015)
For a mass information spread, a speaker is used to reach more people at once. While the use of speaker creates a lot of noise pollution, a dot-matrix display used all around the world to convey message to the public audience is much more convenient and efficient. A dot-matrix led display is a display device used to convey information on machines, clocks, railway departure indicators and many other devices. The display consists of a dot matrix of led lights that works by switching on or off selected lights. A common problem is the display is usually placed at high place to make it visible yet this poses a problem to reprogram the display if there is any new message to be written. The project uses an arduino Uno that communicate with an android phone through a bluetooth module to reprogram a dot-matrix display. Through this, the display can show new message wirelessly using an app used by an android mobile phone.